Maternal body mass index affects embryo morphokinetics: a time-lapse study - Bartolacci, Alessandro; Buratini, Jose [UNESP]; Moutier, Clarissa; Guglielmo, Maria Cristina; Novara, Paola Vittoria; Brambillasca, Fausta; Renzini, Mario Mignini; Dal Canto, Mariabeatrice (Springer, 2019)
PurposeTo assess the effect of body mass index (BMI) on morphokinetic parameters of human embryos evaluated with time-lapse technology during in vitro culture.MethodsA retrospective analysis of ART cycles utilizing time-lapse technology was undertaken to assess the potential impact of maternal BMI on morphokinetic and static morphological parameters of embryo development. The cohort of patients was divided into four groups: 593 embryos from 128 underweight women in group A; 5248 embryos from 1107 normal weight women in group B; 1053 embryos from 226 overweight women in group C; and 286 embryos from 67 obese women in group D.ResultsAfter adjusting for maternal age, paternal age, and cause of infertility, time to reach five blastomeres (t5) and time to reach eight blastomeres (t8) were longer in obese women compared with normoweight women [50.84h (46.31-55.29) vs. 49.24h (45.69-53.22) and 57.89h (51.60-65.94) vs. 55.66h (50.89-62.89), adjusted p<0.05 and adjusted p<0.01, respectively]. In addition, t8 was also delayed in overweight compared with normoweight women [56.72h (51.83-63.92) vs. 55.66h (50.89-62.89), adjusted p<0.01]. No significant differences were observed among groups with regard to embryo morphology and pregnancy rate. Miscarriage rate was higher in underweight compared with normoweight women (OR=2.1; 95% CI 1.12-3.95, adjusted p<0.05).ConclusionAssessment with time-lapse technology but not by classical static morphology evidences that maternal BMI affects embryo development. Maternal obesity and overweight are associated with slower embryo development.
Keywords: BMI; Embryo development; Morphokinetics; Time-lapse